Perforator-base flaps for closure of wound at ankle and distal tibia - Mohd Yusof, Nazri; Sulong, Ahmad Fadzli (2015)
INTRODUCTION: Perforators flap has gained popularity recently in lower limb trauma as reliable methods soft tissue coverage in the distal tibia. It is based on the concept of angiosome that was introduced by Taylor in 1987 to describe the territory of skin supply by perforators. The aim of this study is to describe the surgical technique and the outcome using this flap in orthopaedic patients.